A printed highly stretchable supercapacitor by a combination of carbon ink and polymer network. (November 2021) - Song, Chiho; Chen, Baohong; Hwang, Jeonguk; Lee, Sujin; Suo, Zhigang; Ahn, Heejoon
Abstract: A supercapacitor requires two electronic conductors with large surface areas, separated by an ionic conductor. Here we demonstrate a method to print a highly stretchable supercapacitor. We formulate an ink by mixing graphene flakes and carbon nanotubes with an organic solvent, and use the ink to print two interdigitated electronic conductors on the surface of a dielectric elastomer. We then submerge the printed electronic conductors in an aqueous solution of monomer, photoinitiator, crosslinker, and salt. The organic solvent and water form a binary solvent in which the ions are mobile. Upon UV irradiation, a polymer network forms. In each printed electrode, the graphene flakes and carbon nanotubes form a percolating network, which interpenetrates the polymer network. The electronic and ionic conductors form large interfacial areas. When the supercapacitor is stretched, the graphene flakes and carbon nanotubes slide relative to one another, and the polymer network deforms by entropic elasticity. The polymer network traps individual graphene flakes and carbon nanotubes, so that repeated stretch neither breaks the percolating network nor shorts the two electrodes. The supercapacitor maintains 88% the initial capacitance after 1600 cycles of stretch to five times its initial dimension. The interpenetration of a covalent network of elastic polymer chains and a percolating network of conductive particles is generally applicable for making stretchable ionotronic devices.